The issue of Algerian women’s education in the thought of Sheikh Muhammad al-Bashir al-Ibrahimi - maouchi, amel (The Algerian Historical Journal, 2026)
The issue of women’s education is considered one of the important issues raised by reformers in Algeria, headed by Sheikh Al-Bashir Al-Ibrahimi, who was one of the most important defenders of women’s right to education, considering that the progress of societies depends on educating them and keeping them away from the danger of ignorance, This is what we seek to clarify in this contribution by answering the following problematic: How did the sheikh view the issue of Algerian women's education? We have concluded that Ibrahimi made a great effort to educate women, and link them to their identity and Islamic culture, He stood up to the negative ideas that deprived women of education, and this issue was one of his biggest and most important concerns.